Urgensi Pengawasan Perusahaan Cangkang Sebagai Upaya Penghindaran Tindak Pidana Pencucian Uang Oleh Perusahaan Cangkang di Indonesia - Yundira, Irma; Tiopan, Demson (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
The purpose of this study was to determine the application of law in money laundering crimes with the mode of establishing shell companies using normative juridical research methods. The data used consists of secondary data with statute approach, case approach, comparative approach, and conceptual approach. This research finds that these shell companies have been formed legally, but the legality of their formation does not guarantee the legality of their designation. Therefore, it is necessary to supervise shell companies in order to prevent the rampant cases of laundering through shell companies in Indonesia by adopting the methods used by the United States and India in dealing with shell companies.